2022
DOI: 10.3390/land11101705
|View full text |Cite
|
Sign up to set email alerts
|

Pre/Post-Fire Soil Erosion and Evaluation of Check-Dams Effectiveness in Mediterranean Suburban Catchments Based on Field Measurements and Modeling

Abstract: The present study was conducted in the suburban forest of Thessaloniki city (Seich Sou), which constitutes one of the most significant suburban forests in Greece. In 1997, more than the half of the forest area was destroyed by a wildfire, after which soil erosion and flood control works (check-dams) were constructed in the burned areas. The aim of the study is to estimate the annual soil erosion rate for the last 30 years (pre- and post-fire periods) applying the WaTEM/SEDEM model, in order to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…The apparent return to steady‐state hydrological conditions (or lack of deviation from baseline conditions), and the capacity for hydrological resilience is potentially explained by multiple interacting factors: Intrinsic thresholds were not exceeded: While the percent of area burned in the RRW was sufficiently beyond reported disturbance thresholds (>20%), the lack of hydrological response could be attributed to many factors that are unique to this Mediterranean ecoregion that impart intrinsic thresholds required for change. We hypothesize this could be due to the low/moderately flammable nature of sparse oak woodlands (Curt et al., 2011; Engber et al., 2011), spatial heterogeneity of wildfire severity (Moody et al., 2013), intense drought conditions (Nunes et al., 2020), and lack of post‐wildfire storms to sufficiently exceed infiltration excess and saturation excess flow due to the drought (Margiorou et al., 2022). We hypothesize that sub‐watersheds of the RRW Mediterranean ecoregion have not burned beyond an intrinsic, and still unknown threshold required to initiate change (Peterson et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent return to steady‐state hydrological conditions (or lack of deviation from baseline conditions), and the capacity for hydrological resilience is potentially explained by multiple interacting factors: Intrinsic thresholds were not exceeded: While the percent of area burned in the RRW was sufficiently beyond reported disturbance thresholds (>20%), the lack of hydrological response could be attributed to many factors that are unique to this Mediterranean ecoregion that impart intrinsic thresholds required for change. We hypothesize this could be due to the low/moderately flammable nature of sparse oak woodlands (Curt et al., 2011; Engber et al., 2011), spatial heterogeneity of wildfire severity (Moody et al., 2013), intense drought conditions (Nunes et al., 2020), and lack of post‐wildfire storms to sufficiently exceed infiltration excess and saturation excess flow due to the drought (Margiorou et al., 2022). We hypothesize that sub‐watersheds of the RRW Mediterranean ecoregion have not burned beyond an intrinsic, and still unknown threshold required to initiate change (Peterson et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1997, the forest experienced a devastating wildfire that destroyed more than half of its area. The impact of the 1997 wildfire has been far-reaching, affecting not only the forest ecosystem but also the local community [33]. The data used in the present study were captured from various sites in the Thessaloniki metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…Low RMSE and MAE values indicate better performance of models. Based on previous studies the RMSE values less than half of the SD (Standard Deviation) of the observed data (RMSE/Sdobs < 0.65) may be considered low and acceptable [58,59]. Based on Table 4, this equation applies.…”
Section: Analysis Of Future Precipitationmentioning
confidence: 99%
“…Additionally, R 2 , MAE and RMSE were used to select the best regression relationship for the estimation of the R-factor of the Smith-Wischmeier method. Based on previous studies that RMSE values less than half of the SD (Standard Deviation) of the observed data (RMSE/SD obs < 0.65) may be considered low and acceptable [58,59]. Based on Table 4, this equation applies.…”
Section: Spatial Distribution Of R-factor Erosivity In Current and Fu...mentioning
confidence: 99%